Pelatihan Branding Produk UMKM Berbasis Media Sosial Untuk Wirausaha Muda di Ciputat, Tangerang Selatan: Desain Logo, Feed Instagram dan Storytelling Produk Secara Digital - Alamsyah, Alamsyah; Sari , Dyan Prawita; Sukma , Agus Hitopa Sukma; Nawangwulan, Irma M; Anantadjaya, Samuel PD (Prisani Cendekia, 2024)
Social media-based product branding is one of the keys to the success of MSMEs in building identity and increasing competitiveness amidst an increasingly competitive digital market. In the Ciputat area, South Tangerang, many young entrepreneurs have business potential but still face limitations in designing effective digital branding strategies. Responding to this challenge, this community service activity is designed to increase the digital branding capacity of young entrepreneurs through logo design training, Instagram feed management, and the preparation of communicative and attractive product storytelling. This activity is carried out with a participatory approach through the stages of identifying participant needs, preparing contextual training modules, practicing direct content design and production, and evaluating participant abilities through pre-tests and post-tests. The training results showed a significant increase in the understanding of the concept of digital branding and the technical skills of participants in creating consistent visual elements and conveying product value through narratives on social media. This program is expected to strengthen the brand identity of MSMEs and open up opportunities for digital market expansion for young entrepreneurs in the area.